Resource to Develop Medical Students into Peer Mentors - Sean Meredith; Larrie Greenberg; Benjamin Blatt (Association of American Medical Colleges, 2014)
Abstract The primary goal of the Peer Mentoring Guide is to develop fourth year medical students (MS-4s) into mentors for first year medical students (MS-1s). The purpose of this resource is to provide others who want to develop a peer mentoring program as part of an advanced students-as-teachers curriculum. The George Washington University was one of the first schools to have a program to prepare medical students for their teaching role as residents and practicing physicians, which was called TALKS (Teaching and Learning Knowledge and Skills). We recently recognized that some participants were interested in going beyond the boundaries of the program to learn advanced teaching skills. Thus, we created an Advanced TALKS program to meet this demand. Peer mentoring was the primary focus for the Advanced TALKS program. For this program we developed the Peer Mentoring Guide presented here for others to use as a resource. There has been increasing recognition of the need to prepare medical students for their teaching role as residents and practicing physicians.1 In one review of the literature, 39 programs were identified where students were trained to be teachers. The roles taken on by the student teacher included portraying standardized patients, tutoring students in academic trouble, teaching clinical skills, simulating a learner, administering an elective course, and teaching peers. Though a recent survey of US medical schools documented 43 formal programs in the 99 schools that responded to the survey, almost all of the other schools had informal programs.2 In addition, there is a growing literature on the value of near peer teaching programs.1,2,3 The course was piloted at our institution with a small group of MS4s (N=5). Although MS4s are a select group and this limits the numbers, the intention was to provide an educational experience that went beyond the general education elective at GWU (the TALKS course) to individuals who wanted more. We created the mentoring program for those students with further interest as an addition to their current curriculum. Over the course of an academic year, the students all completed 2 workshops and then a longitudinal mentoring experience with first year medical students.